Позитивні та негативні граматичні девіації прикметників сучасної української мови - Рязанцева, Дар’я В.; Riazantseva, D. V. (Волинський національний університет імені Лесі Українки, 2012)
У статті розглядаються порушення мовних норм, граматичні девіації на матеріалі прикметників сучасної української мови. Аналізуються випадки порушення мовних норм як ефективного засобу для створення граматичного значення оцінки та негативні тенденції у сучасній мові. The article considers positive and negative aspects of breaking the rules and standards of modern language on the material of adjectives of Ukrainian language. Theoretical description of the usage of wrong forms of adjectives as the effective way of creating estimation meaning in the newspaper texts has been represented in this article.
The positive and the negative grammatical deviations of the adjectives of Ukrainian language
Keywords: мовна норма; language standard; граматична девіація; deviation; оцінка; estimation meaning; українська мова; Ukrainian language